Antifogging agent composition and antifogging article having antifogging film formed from said composition
The antifogging agent composition addresses solvent cracks and transparency issues by using a copolymer, blocked polyisocyanate curing agent, colloidal silica, and surfactant, resulting in a film with enhanced fogging properties and water resistance.
Patent Information
- Application Number
- JP2022507141
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-10
- Filing Date
- 2021-03-05
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-03-05
Smart Images

Figure 0007619359000001 
Figure 0007619359000002 
Figure 0007619359000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an antifogging agent composition and an antifogging article having an antifogging film formed from the composition. [Background technology]
[0002] In vehicle lighting such as automobile headlamps, high humidity air may enter the lamp chamber, and the lens may be cooled by the outside air or rainfall, causing moisture to condense on the inner surface, resulting in fogging. As a result, the brightness of the vehicle light may decrease and the aesthetic appearance of the lens surface may be impaired, causing discomfort to the user. To prevent such fogging of the lens, a method of applying an anti-fogging agent to the area where fogging occurs is known (Patent Documents 1 to 5).
[0003] Here, Patent Document 2 describes that the antifogging agent composition described in Patent Document 1 has a problem in that the solvent used is highly corrosive to the substrate, and therefore corrodes the substrate polycarbonate or polymethyl methacrylate, causing solvent cracks (a phenomenon in which the solvent corrodes the substrate during application and drying of a coating liquid, causing cracks and fissures in the substrate). Patent Document 2 discloses the provision of an antifogging composition containing a specific alcohol and glycol ether-based solvent as the main solvent, with the aim of suppressing such solvent cracks. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-140589 A [Patent Document 2] JP 2016-27134 A [Patent Document 3] JP 2019-6881 A [Patent Document 4] International Publication No. 2009 / 044912 [Patent Document 5] JP 2008-308661 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, it has been found that the antifogging agent composition disclosed in Patent Document 2 is insufficient in suppressing solvent cracking in substrates with relatively high internal stress, such as large injection-molded products and injection-molded products with complex shapes. The antifogging agent composition disclosed in Patent Document 3 also contains a large amount of organic solvent, and thus there are concerns about the suppression of solvent cracking.
[0006] On the other hand, the anti-fogging film formed from the anti-fogging agent composition is required to have anti-fogging properties, adhesion to the substrate, and water resistance, as disclosed in Patent Document 3. In addition, the anti-fogging agents disclosed in Patent Documents 4 and 5 have a problem of insufficient transparency due to insufficient compatibility between metal oxides such as colloidal silica and copolymers such as acrylates.
[0007] The present invention has been made in view of the above-mentioned circumstances, and has an object to provide an antifogging composition which is excellent in suppressing solvent cracking during coating, drying and heat curing of the antifogging composition, and which can form an antifogging film which is excellent in antifogging properties, adhesion, water resistance and transparency. [Means for solving the problem]
[0008] That is, the present invention provides an antifogging agent composition comprising a copolymer (A), a blocked polyisocyanate curing agent (B), a colloidal silica (C), a surfactant (D) and water (E), wherein the copolymer (A) is represented by the general formula (1): [ka] (In general formula (1), R 1 is a hydrogen atom or a methyl group, and R 2 and R 3are independently a straight-chain or branched-chain alkyl group having 1 to 8 carbon atoms.) and an N,N-dialkyl(meth)acrylamide monomer (a-1) represented by the general formula (2): [ka] (In general formula (2), R 4 is a hydrogen atom or a methyl group, and n is an integer of 1 to 10.) and a hydroxyalkyl (meth)acrylate monomer (a-2) represented by the general formula (3): [ka] (In general formula (3), R 5 is a hydrogen atom or a methyl group, and R 6 is a straight-chain, branched-chain, or cyclic hydrocarbon group having 1 to 22 carbon atoms.), and the amount of the blocked polyisocyanate curing agent (B) is 35 to 300 parts by mass, the amount of the colloidal silica (C) is 80 parts by mass or more and 600 parts by mass or less, and the amount of the water (E) is 650 parts by mass or more, relative to 100 parts by mass of the copolymer (A).
[0009] The present invention also relates to an anti-fogging article having an anti-fogging film formed from the anti-fogging agent composition on a substrate. Effect of the Invention
[0010] Although the details of the mechanism of action of the antifogging agent composition, antifogging film, and antifogging article of the present invention are unclear, it is presumed as follows. However, the present invention does not need to be interpreted as being limited to this mechanism of action.
[0011] The antifogging agent composition of the present invention contains copolymer (A), blocked polyisocyanate curing agent (B), colloidal silica (C), surfactant (D) and water (E). The copolymer (A) contains the monomers (a-1) to (a-3), so that the antifogging property of the antifogging film is mainly enhanced based on the monomer (a-1), the compatibility between the copolymer (A) and the colloidal silica (C) is enhanced based on the monomer (a-2), and the transparency of the antifogging film is enhanced. In addition, the crosslinking structure can be formed with the blocked polyisocyanate curing agent (B), so that the water resistance of the antifogging film is enhanced, and the water resistance of the antifogging film is enhanced based on the monomer (a-3), so that an antifogging agent composition capable of forming an antifogging film having excellent antifogging property, adhesion, water resistance and transparency can be obtained. In addition, the antifogging agent composition of the present invention contains a specific amount of colloidal silica (C), so that the water resistance of the antifogging film can be further enhanced. Furthermore, since the antifogging agent composition of the present invention contains a specific amount of water (E), the content of the organic solvent is reduced, making it possible to suppress solvent cracking of the substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The antifogging agent composition of the present invention contains a copolymer (A), a blocked polyisocyanate curing agent (B), colloidal silica (C), a surfactant (D) and water (E).
[0013] <Copolymer (A)> The copolymer (A) of the present invention is a (meth)acrylate copolymer obtained from a monomer mixture, and the monomer mixture contains at least the following monomers (a-1) to (a-3):
[0014] <Monomer (a-1)> The monomer (a-1) of the present invention is represented by the general formula (1): [ka] (In general formula (1), R 1 is a hydrogen atom or a methyl group, and R 2 and R 3are independently a straight-chain or branched-chain alkyl group having 1 to 8 carbon atoms.)
[0015] In the general formula (1), examples of the linear or branched alkyl group having 1 to 8 carbon atoms include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, n-amyl, i-amyl, t-amyl, n-hexyl, n-octyl, and 2-ethylhexyl groups. From the viewpoint of enhancing the antifogging performance of the antifogging film, the alkyl group is preferably a linear or branched alkyl group having 1 to 4 carbon atoms, more preferably a methyl group or an ethyl group, and even more preferably a methyl group. The monomer (a-1) may be used alone or in combination of two or more kinds.
[0016] <Monomer (a-2)> The monomer (a-2) of the present invention is represented by the general formula (2): [ka] (In general formula (2), R 4 is a hydrogen atom or a methyl group, and n is an integer of 1 to 10.
[0017] In the general formula (2), from the viewpoint of increasing the transparency of the anti-fogging film, n is preferably an integer of 1 to 5. The monomer (a-2) may be used alone or in combination of two or more kinds.
[0018] The monomer (a-3) of the present invention is represented by the general formula (3): [ka] (In general formula (3), R 5 is a hydrogen atom or a methyl group, and R 6is a straight-chain, branched-chain, or cyclic hydrocarbon group having 1 to 22 carbon atoms.
[0019] In the general formula (3), examples of the linear, branched, or cyclic hydrocarbon group having 1 to 22 carbon atoms include alkyl groups such as methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, n-amyl, i-amyl, t-amyl, n-hexyl, cyclohexyl, n-octyl, 2-ethylhexyl, n-nonyl, isobornyl, lauryl, myristyl, cetyl, stearyl, and behenyl; alkenyl groups such as oleyl; and aryl groups such as phenyl. From the viewpoint of enhancing the water resistance of the anti-fogging film, the hydrocarbon group is preferably a linear, branched, or cyclic hydrocarbon group having 2 to 18 carbon atoms, and more preferably a linear, branched, or cyclic hydrocarbon group having 4 to 16 carbon atoms. The monomer (a-3) may be used alone or in combination of two or more kinds.
[0020] The monomer (a-1) is preferably 20 to 90 parts by mass in a total of 100 parts by mass of the monomer (a-1), the monomer (a-2), and the monomer (a-3). From the viewpoint of improving the antifogging properties of the antifogging film, the monomer (a-1) is more preferably 30 parts by mass or more, even more preferably 40 parts by mass or more, and even more preferably 50 parts by mass or more in a total of 100 parts by mass of the monomer (a-1), the monomer (a-2), and the monomer (a-3), and from the viewpoint of improving the water resistance of the antifogging film, the monomer (a-1) is more preferably 80 parts by mass or less, and even more preferably 70 parts by mass or less.
[0021] The monomer (a-2) is preferably 5 to 50 parts by mass in a total of 100 parts by mass of the monomer (a-1), the monomer (a-2), and the monomer (a-3). From the viewpoint of improving the transparency of the anti-fogging film, the monomer (a-2) is more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, in a total of 100 parts by mass of the monomer (a-1), the monomer (a-2), and the monomer (a-3), and from the viewpoint of improving the anti-fogging property of the anti-fogging film, the monomer (a-2) is more preferably 40 parts by mass or less, and even more preferably 35 parts by mass or less.
[0022] The monomer (a-3) is preferably 1 to 40 parts by mass in a total of 100 parts by mass of the monomer (a-1), the monomer (a-2), and the monomer (a-3). From the viewpoint of improving the water resistance of the anti-fogging film, the monomer (a-3) is more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, in a total of 100 parts by mass of the monomer (a-1), the monomer (a-2), and the monomer (a-3), and from the viewpoint of improving the anti-fogging property of the anti-fogging film, the monomer (a-3) is more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less.
[0023] In the monomer mixture, the total proportion of the monomer (a-1), the monomer (a-2), and the monomer (a-3) is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more.
[0024] From the viewpoint of improving the water resistance of the anti-fogging film, the monomer mixture may contain the following monomer (a-4) and / or monomer (a-5).
[0025] The monomer (a-4) of the present invention is represented by the general formula (4): [ka] (In general formula (4), R 7 is a hydrogen atom or a methyl group, and R 8is a straight-chain or branched-chain alkylene group having 1 to 8 carbon atoms.
[0026] The monomer (a-5) of the present invention is represented by the general formula (5): [ka] (In general formula (5), R 9 is a hydrogen atom or a methyl group, and R 10 is a straight-chain or branched-chain alkylene group having 1 to 8 carbon atoms.
[0027] In the general formula (4), examples of the linear or branched alkylene group having 1 to 8 carbon atoms include a methylene group, an ethylene group, an n-propylene group, an n-butylene group, an i-butylene group, an n-pentylene group, an n-hexylene group, and an n-octylene group. From the viewpoint of enhancing the antifogging properties of the antifogging film, the alkylene group is preferably a linear alkylene group having 1 to 4 carbon atoms. The monomer (a-4) may be used alone or in combination of two or more kinds.
[0028] In the general formula (5), examples of the linear or branched alkylene group having 1 to 8 carbon atoms include a methylene group, an ethylene group, an n-propylene group, an n-butylene group, an i-butylene group, an n-pentylene group, an n-hexylene group, and an n-octylene group. From the viewpoint of enhancing the antifogging properties of the antifogging film, the alkylene group is preferably a linear alkylene group having 1 to 4 carbon atoms. The monomer (a-5) may be used alone or in combination of two or more kinds.
[0029] When the monomer (a-4) and / or the monomer (a-5) are used, the amount of the monomer (a-4) and / or the monomer (a-5) is preferably 30 parts by mass or less, and more preferably 15 parts by mass or less, per 100 parts by mass in total of the monomer (a-1), the monomer (a-2), and the monomer (a-3), from the viewpoint of improving the adhesion of the anti-fogging film.
[0030] When the monomer (a-4) and / or the monomer (a-5) are used, the total proportion of the monomer (a-1), the monomer (a-2), the monomer (a-3), the monomer (a-4) and / or the monomer (a-5) in the monomer mixture is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more.
[0031] <Method for producing copolymer (A)> The copolymer (A) of the present invention is obtained by copolymerizing the monomer mixture. The copolymer structure may be any of random copolymers, alternating copolymers, block copolymers and graft copolymers, but a random copolymer is preferred from the viewpoint of improving the effects of the antifogging agent composition, including antifogging properties, and easily preparing the antifogging agent composition. As a polymerization method for obtaining the copolymer, various known polymerization methods such as radical polymerization, cationic polymerization, anionic living polymerization and cationic living polymerization are adopted, but the radical polymerization method is preferred from the viewpoint of ease of industrial productivity and wide-ranging performance. As the radical polymerization method, a normal bulk polymerization method, suspension polymerization method, solution polymerization method, emulsion polymerization method and the like are adopted, but the solution polymerization method is preferred from the viewpoint that it can be used as an antifogging agent composition as it is after polymerization.
[0032] Examples of the polymerization solvent used in the solution polymerization method include water, methanol, ethanol, propanol, i-propanol, diacetone alcohol, and other alcohol-based solvents; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, 3-methoxybutanol, 3-methoxy-3-methylbutanol, and other alcohol ether-based solvents; acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and other ketone-based solvents; tetrahydrofuran, dioxane, and other ether-based solvents; methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, t-butyl acetate, methyl lactate, ethyl lactate, and other ester-based solvents; benzene, toluene, xylene, and other aromatic solvents; formamide, dimethylformamide, and other amide-based solvents. Among these, water, alcohol-based solvents, and alcohol ether-based solvents are preferred. The polymerization solvents may be used alone or in combination of two or more.
[0033] The radical polymerization initiator may be a commonly used organic peroxide, an azo compound, or the like. Examples of the organic peroxide include benzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-hexanoate, t-butylperoxypivalate, and t-hexylperoxypivalate. Examples of the azo compound include 2,2'-azobisisobutyronitrile and 2,2'-azobis-2-methylbutyronitrile. The radical polymerization initiator may be used alone or in combination of two or more kinds.
[0034] The amount of the radical polymerization initiator added is preferably 0.01 to 5 parts by mass relative to 100 parts by mass of the monomer mixture. The radical polymerization initiator is preferably added dropwise to a reaction vessel while polymerization is carried out, since this makes it easier to control heat generated by polymerization. The temperature at which the polymerization reaction is carried out is appropriately changed depending on the type of radical polymerization initiator used, but is preferably 30 to 150°C, more preferably 40 to 100°C, in terms of industrial production.
[0035] From the viewpoint of imparting water resistance to the anti-fog film, the number average molecular weight (Mn) of the copolymer (A) is preferably 3,000 or more, and more preferably 5,000 or more. From the viewpoint of improving the coatability and handleability of the anti-fog agent composition, the number average molecular weight (Mn) of the copolymer (A) is preferably 300,000 or less, and more preferably 200,000 or less.
[0036] The number average molecular weight (Mn) of the copolymer (A) can be determined by a GPC method. <Measurement conditions for number average molecular weight (Mn)> Analytical equipment: HLC-8320GPC (manufactured by Tosoh Corporation) Guard column: TSKgel guard column SuperMP(HZ)M (manufactured by Tosoh Corporation) First column: TSK gel column multipore HZ-M (manufactured by Tosoh Corporation) Second column: TSK gel column multipore HZ-M (manufactured by Tosoh Corporation) Detector: differential refractometer Column temperature: 40℃ Developing solvent: Tetrahydrofuran Reference material: polystyrene Flow rate: 0.350mL / min Sample concentration: 0.2% by mass Injection volume: 10μL
[0037] The amount of OH mol contained in 100 parts by mass of the copolymer A is calculated by the following formula. Formula: {parts by mass of monomer having a hydroxyl group per 100 parts by mass of the total of monomers constituting copolymer A} / {molecular weight of monomer having a hydroxyl group}
[0038] <Blocked polyisocyanate curing agent (B)> The blocked polyisocyanate curing agent (B) of the present invention is a compound having two or more blocked isocyanate groups. The blocked polyisocyanate curing agent (B) may be used alone or in combination of two or more kinds.
[0039] Examples of the blocked polyisocyanate curing agent (B) include hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, xylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, and the like, as well as products produced by blocking isocyanate groups contained in polyisocyanate derivatives such as their biuret derivatives, isocyanurate derivatives, and adducts with trimethylolpropane with a blocking agent.
[0040] Examples of the blocking agent include alcohols such as methanol, ethanol, n-propanol, i-propanol, n-butanol, and 1-methoxy-2-propanol; oximes such as formamide oxime, acetaldoxime, acetoxime, methylethylketoxime, diacetylmonoxime, benzophenone oxime, and cyclohexanone oxime; pyrazoles such as dimethylpyrazole, diethylpyrazole, and diisopropylpyrazole; and dialkyl malonates such as dimethyl malonate, diethyl malonate, dipropyl malonate, and dibutyl malonate. The blocking agent is preferably pyrazoles, oximes, and dialkyl malonates from the viewpoint of being cured at a low temperature and in a short time, and more preferably dimethylpyrazole, diethylpyrazole, acetoxime, methylethylketoxime, dimethyl malonate, and diethyl malonate.
[0041] Examples of commercially available blocked polyisocyanate curing agents (B) include trade names: "Duranate MF-K60B", "Duranate SBB-70P", "Duranate SBN-70D", "Duranate MF-B60B", "Duranate 17B-60P", "Duranate TPA-B80E", "Duranate E420-B80B", "Duranate WM44-L70G" (all manufactured by Asahi Kasei Corporation), trade names: "Aqua BI200", "Aqua BI220" (all manufactured by Baxenden), trade names: "Meikanate CX", "SU268A" (all manufactured by Meisei Chemical Industry Co., Ltd.), trade names: "Coronate BI-301", "Coronate 2507", "Coronate 2554" (all manufactured by Tosoh Corporation), and the like.
[0042] The blocked polyisocyanate curing agent (B) of the present invention may be a (meth)acrylate polymer and / or copolymer having a blocked isocyanate group. The (meth)acrylate polymer and / or copolymer having a blocked isocyanate group is a polymer obtained from a vinyl monomer having a blocked isocyanate group, or a copolymer obtained from a monomer mixture containing a radical polymerizable vinyl monomer having a blocked isocyanate group and a copolymerizable radical polymerizable vinyl monomer not having a blocked isocyanate group.
[0043] Examples of the vinyl monomer having a blocked isocyanate group include compounds obtained by blocking a vinyl monomer having an isocyanate group with a blocking agent, such as isocyanate ethyl (meth)acrylate, isocyanate ethyl (meth)acrylamide, isocyanate propyl (meth)acrylate, isocyanate propyl (meth)acrylamide, isocyanate butyl (meth)acrylate, isocyanate butyl (meth)acrylamide, etc. Examples of the blocking agent include alcohols, oximes, active methylenes, and pyrazoles, and oximes, active methylenes, and pyrazoles are preferred in terms of deblocking efficiency. The oximes are not particularly limited, and examples thereof include formamide oxime, acetaldoxime, acetoxime, methyl ethyl ketoxime, diacetyl monooxime, benzophenone oxime, and cyclohexanone oxime. The active methylenes are not particularly limited, and examples thereof include dimethyl malonate, diethyl malonate, ethyl acetoacetate, methyl acetoacetate, and acetylacetone. The pyrazoles are not particularly limited, and examples thereof include dimethylpyrazole, diethylpyrazole, and diisopropylpyrazole.
[0044] Examples of the vinyl monomer having no blocked isocyanate group include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, ethylhexyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, ceyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and dicyclopentadienyl (meth)acrylate; (meth)acrylamide, dimethyl (meth)acrylamide, diethyl (meth)acrylamide, dipropyl (meth)acrylamide, dibutyl (meth)acrylamide, diphenyl ether ... Dialkyl (meth)acrylamides such as octyl (meth)acrylamide; morpholine-containing vinyl compounds such as (meth)acroyl morpholine and (meth)allyl morpholine; sulfonic acid group-containing vinyl monomers such as sulfoethyl (meth)acrylate, sodium sulfoethyl (meth)acrylate, t-butyl (meth)acrylamidosulfonic acid and sodium t-butyl (meth)acrylamidosulfonate; (meth)acrylic acid or salt compounds thereof such as (meth)acrylic acid, sodium (meth)acrylate and potassium (meth)acrylate; glycidyl (meth)acrylate; trifluoroethyl (meth)acrylate; polysiloxane-containing (meth)acrylate; aromatic vinyl compounds such as styrene, vinyl toluene and α-methylstyrene; Examples of suitable vinyl cyanide compounds include acrylonitrile and methacrylonitrile; amino group-containing (meth)acrylates such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and diethylaminopropyl (meth)acrylate; alkylene oxide-modified (meth)acrylates such as methoxy-terminated polyethylene glycol (meth)acrylate and methoxy-terminated polypropylene glycol (meth)acrylate; vinyl acetate compounds such as vinyl acetate, vinyl chloroacetate, and vinyl trifluoroacetate; and vinyl amide compounds such as N-vinylformamide, N-vinylacetamide, and N-vinylpyrrolidone.
[0045] In order to improve the transparency of the anti-fogging film, the (meth)acrylate copolymer having a blocked isocyanate group is represented by the general formula (6): [ka] (In general formula (6), R 11 is a hydrogen atom or a methyl group, and R 12 and R 13 are independently a straight-chain or branched-chain alkyl group having 1 to 8 carbon atoms; and General formula (7): [ka] (In general formula (7), R 14 is a hydrogen atom or a methyl group, and R 15 is a residue derived from a blocking agent. General formula (8): [ka] (In general formula (8), R 16 is a hydrogen atom or a methyl group, and R 17 is a straight-chain, branched-chain, or cyclic hydrocarbon group having 1 to 22 carbon atoms.
[0046] In the general formula (6), examples of the linear or branched alkyl group having 1 to 8 carbon atoms include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, n-amyl, i-amyl, t-amyl, n-hexyl, n-octyl, and 2-ethylhexyl groups. From the viewpoint of enhancing the antifogging performance of the antifogging film, the alkyl group is preferably a linear or branched alkyl group having 1 to 4 carbon atoms, more preferably a methyl group or an ethyl group, and even more preferably a methyl group. The monomer (b-1) may be used alone or in combination of two or more kinds.
[0047] In the general formula (7), examples of the residue derived from the blocking agent include alcohols such as methanol, ethanol, n-propanol, i-propanol, n-butanol, and 1-methoxy-2-propanol; oximes such as formamide oxime, acetaldoxime, acetoxime, methyl ethyl ketoxime, diacetyl monooxime, benzophenone oxime, and cyclohexanone oxime; pyrazoles such as dimethylpyrazole, diethylpyrazole, and diisopropylpyrazole; and dialkyl malonates such as dimethyl malonate, diethyl malonate, dipropyl malonate, and dibutyl malonate. From the viewpoint of being able to cure at a low temperature and in a short time, the residue derived from the blocking agent is preferably a pyrazole, an oxime, or a dialkyl malonate, and more preferably dimethylpyrazole, diethylpyrazole, acetoxime, methyl ethyl ketoxime, dimethyl malonate, or diethyl malonate. The monomer (b-2) may be used alone or in combination of two or more kinds.
[0048] In the general formula (8), examples of the linear, branched, or cyclic hydrocarbon group having 1 to 22 carbon atoms include alkyl groups such as methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, n-amyl, i-amyl, t-amyl, n-hexyl, cyclohexyl, n-octyl, 2-ethylhexyl, n-nonyl, isobornyl, lauryl, myristyl, cetyl, stearyl, and behenyl; alkenyl groups such as oleyl; and aryl groups such as phenyl. From the viewpoint of enhancing the water resistance of the antifogging film, the hydrocarbon group is preferably a linear, branched, or cyclic hydrocarbon group having 2 to 18 carbon atoms, and more preferably a linear, branched, or cyclic hydrocarbon group having 4 to 16 carbon atoms. The monomer (b-3) may be used alone or in combination of two or more kinds.
[0049] The amount of the monomer (b-1) is preferably 20 to 90 parts by mass in a total of 100 parts by mass of the monomer (b-1), the monomer (b-2), and the monomer (b-3). From the viewpoint of improving the antifogging properties of the antifogging film, the amount of the monomer (b-1) in a total of 100 parts by mass of the monomer (b-1), the monomer (b-2), and the monomer (b-3) is more preferably 30 parts by mass or more, and even more preferably 40 parts by mass or more, and from the viewpoint of improving the water resistance of the antifogging film, it is more preferably 80 parts by mass or less, and even more preferably 70 parts by mass or less.
[0050] The amount of the monomer (b-2) is preferably 5 to 50 parts by mass in a total of 100 parts by mass of the monomer (b-1), the monomer (b-2) and the monomer (b-3). From the viewpoint of improving the water resistance of the anti-fogging film, the amount of the monomer (b-2) in a total of 100 parts by mass of the monomer (b-1), the monomer (b-2) and the monomer (b-3) is more preferably 10 parts by mass or more, and from the viewpoint of improving the adhesion of the anti-fogging film, it is more preferably 45 parts by mass or less, and even more preferably 35 parts by mass or less.
[0051] The amount of the monomer (b-3) is preferably 1 to 40 parts by mass in a total of 100 parts by mass of the monomer (b-1), the monomer (b-2), and the monomer (b-3). From the viewpoint of improving the water resistance of the anti-fogging film, the amount of the monomer (b-3) in a total of 100 parts by mass of the monomer (b-1), the monomer (b-2), and the monomer (b-3) is more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, and from the viewpoint of improving the anti-fogging property of the anti-fogging film, it is more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less.
[0052] The blocked polyisocyanate curing agent (B) is present in an amount of 35 parts by mass or more and 300 parts by mass or less relative to 100 parts by mass of the copolymer (A). From the viewpoint of improving the water resistance of the anti-fogging film, the blocked polyisocyanate curing agent (B) is present in an amount of preferably 50 parts by mass or more and more preferably 70 parts by mass or more relative to 100 parts by mass of the copolymer (A), and from the viewpoint of improving adhesion, the blocked polyisocyanate curing agent (B) is present in an amount of preferably 250 parts by mass or less and more preferably 200 parts by mass or less.
[0053] In addition, the copolymer (A) and the blocked polyisocyanate curing agent (B) preferably have an NCO / OH ratio (hereinafter, NCO / OH ratio) between the isocyanate group content (NCO) generated after the blocking agent of the blocked isocyanate group contained in the blocked polyisocyanate curing agent (B) is deblocked and the hydroxyl group content (OH) of the copolymer (A) in the range of 0.2 to 2.5. From the viewpoint of improving the water resistance of the anti-fogging film, the NCO / OH ratio is more preferably 0.3 or more, and even more preferably 0.5 or more, and from the viewpoint of improving adhesion, the NCO / OH ratio is more preferably 2.0 or less, and even more preferably 1.5 or less.
[0054] <Method for producing (meth)acrylate polymer and / or copolymer having blocked isocyanate group> The (meth)acrylate polymer and / or copolymer having a blocked isocyanate group of the present invention can be obtained by copolymerizing the monomer mixture. The copolymer structure may be any of random copolymers, alternating copolymers, block copolymers, and graft copolymers, but a random copolymer is preferred from the viewpoint of improving the effects of the antifogging agent composition, including antifogging properties, and easily preparing the antifogging agent composition. As a polymerization method for obtaining the copolymer, various known polymerization methods such as radical polymerization, cationic polymerization, anionic living polymerization, and cationic living polymerization are adopted, but radical polymerization is preferred from the viewpoint of ease of industrial productivity and versatile performance. As the radical polymerization method, a normal bulk polymerization method, suspension polymerization method, solution polymerization method, emulsion polymerization method, etc. are adopted, but a solution polymerization method is preferred from the viewpoint that it can be used as an antifogging agent composition as it is after polymerization.
[0055] Examples of the polymerization solvent used in the solution polymerization method include water, methanol, ethanol, propanol, i-propanol, diacetone alcohol, and other alcohol-based solvents; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, 3-methoxybutanol, 3-methoxy-3-methylbutanol, and other alcohol ether-based solvents; acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and other ketone-based solvents; tetrahydrofuran, dioxane, and other ether-based solvents; methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, t-butyl acetate, methyl lactate, ethyl lactate, and other ester-based solvents; benzene, toluene, xylene, and other aromatic solvents; formamide, dimethylformamide, and other amide-based solvents. Among these, water, alcohol-based solvents, and alcohol ether-based solvents are preferred. The polymerization solvents may be used alone or in combination of two or more.
[0056] The radical polymerization initiator may be a commonly used organic peroxide, an azo compound, or the like. Examples of the organic peroxide include benzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, t-butylperoxy-2-hexanoate, t-butylperoxypivalate, and t-hexylperoxypivalate. Examples of the azo compound include 2,2'-azobisisobutyronitrile and 2,2'-azobis-2-methylbutyronitrile. The radical polymerization initiator may be used alone or in combination of two or more kinds.
[0057] The amount of the radical polymerization initiator added is preferably 0.01 to 5 parts by mass relative to 100 parts by mass of the monomer mixture. The radical polymerization initiator is preferably added dropwise to a reaction vessel while polymerization is carried out, since this makes it easier to control heat generated by polymerization. The temperature at which the polymerization reaction is carried out is appropriately changed depending on the type of radical polymerization initiator used, but is preferably 30 to 150°C, more preferably 40 to 100°C, in terms of industrial production.
[0058] The number average molecular weight (Mn) of the (meth)acrylate polymer and / or copolymer having a blocked isocyanate group is preferably 1,000 or more, more preferably 3,000 or more, from the viewpoint of imparting water resistance to the anti-fogging film. The number average molecular weight (Mn) of the copolymer (A) is preferably 300,000 or less, more preferably 200,000 or less, from the viewpoint of improving the coatability and handleability of the anti-fogging agent composition.
[0059] The number average molecular weight (Mn) of the acrylate polymer and / or copolymer having a blocked isocyanate group can be determined by a GPC method. <Measurement conditions for number average molecular weight (Mn)> Analytical equipment: HLC-8320GPC (manufactured by Tosoh Corporation) Guard column: TSKgel guard column SuperMP(HZ)M (manufactured by Tosoh Corporation) First column: TSK gel column multipore HZ-M (manufactured by Tosoh Corporation) Second column: TSK gel column multipore HZ-M (manufactured by Tosoh Corporation) Detector: differential refractometer Column temperature: 40℃ Developing solvent: Tetrahydrofuran Reference material: polystyrene Flow rate: 0.350mL / min Sample concentration: 0.2% by mass Injection volume: 10μL
[0060] The NCO mol contained in 100 parts by mass of the (meth)acrylate polymer and / or copolymer (B) having a blocked isocyanate group is calculated by the following formula. Formula: {parts by mass of monomer having a blocked isocyanate group per 100 parts by mass of the total of monomers constituting copolymer (B)} / {molecular weight of monomer having a blocked isocyanate group}
[0061] <Colloidal Silica (C)> The colloidal silica (C) of the present invention is in a state in which silica particles represented by the chemical formula of SiO2 are dispersed in a medium to form a colloid. Examples of the medium include methanol, ethanol, i-propyl alcohol, n-butanol, xylene, dimethylformamide, and water. Among these, methanol, ethanol, and water are preferred, and water is more preferred. The colloidal silica (C) may also be one in which the surface of the silica particles is modified with a surface treatment agent such as a silane compound. The colloidal silica (C) may be used alone or in combination of two or more kinds.
[0062] The colloidal silica (C) preferably has an average particle size of 10 to 100 nm, more preferably 10 to 30 nm. The average particle size is an average primary particle size, and is represented by the median diameter (D50) of the volume-based particle size distribution measured by dynamic light scattering. If the average particle size is less than 10 nm, the adhesion of the anti-fogging film to the substrate tends to decrease, and if it exceeds 100 nm, the transparency of the anti-fogging film tends to decrease. The shape of the colloidal silica (C) may be particulate, chain-like, pearl necklace-like, or the like. Among these, the particulate shape is preferable in terms of increasing the transparency of the anti-fogging film.
[0063] Commercially available colloidal silica (C) includes, for example, trade names such as "Snowtex-XS", "Snowtex-S", "Snowtex-30", "Snowtex-50-T", "Snowtex-30L", "Snowtex-YL", "Snowtex-ZL", "Snowtex-MP-1040", "Snowtex-UP", "Snowtex-PS-S", "Snowtex-PS-M", "Snowtex-OXS", "Snowtex-OS", "Snowtex-O", "Snowtex-O-40", "Snowtex-O-50-T", "Snowtex-O-40-T", "Snowtex-O-5 ... 0", "Snowtex-OL", "Snowtex-OYL", "Snowtex-OUP", "Snowtex-PS-SO", "Snowtex-PS-MO", "Snowtex-NXS", "Snowtex-NS", "Snowtex-N", "Snowtex-N-40", "Snowtex-CXS", "Snowtex-C", "Snowtex-CM", "Snowtex-AK", "Snowtex-AK-L" and "Snowtex-AK-Y" (all manufactured by Nissan Chemical Co., Ltd.). Among these, "Snowtex-O", "Snowtex-O-40", "Snowtex-OL", "Snowtex-OYL", "Snowtex-N" and "Snowtex-N-40" are preferred, which have an average particle size of 10 to 100 nm and a particulate shape, and "Snowtex-O", "Snowtex-O-40", "Snowtex-N" and "Snowtex-N-40" are more preferred, which have an average particle size of 10 to 30 nm and a particulate shape.
[0064] The amount of the colloidal silica (C) is 80 parts by mass or more and 600 parts by mass or less relative to 100 parts by mass of the copolymer (A). From the viewpoint of improving the water resistance of the anti-fogging film, the amount of the colloidal silica (C) is preferably 100 parts by mass or more and more preferably 150 parts by mass or more relative to 100 parts by mass of the copolymer (A), and from the viewpoint of improving adhesion and transparency, the amount is preferably 400 parts by mass or less and more preferably 300 parts by mass or less.
[0065] <Surfactant (D)> The surfactant (D) of the present invention is at least one selected from the group consisting of anionic surfactants, cationic surfactants, nonionic surfactants and amphoteric surfactants.
[0066] Examples of the anionic surfactant include fatty acid salts such as fatty acid alkali metal salts such as sodium oleate and potassium oleate; higher alcohol sulfates such as sodium lauryl sulfate and ammonium lauryl sulfate; alkylbenzenesulfonates and alkylnaphthalenesulfonates such as sodium dodecylbenzenesulfonate and sodium alkylnaphthalenesulfonate; polyoxyethylene sulfate salts such as naphthalenesulfonate-formaldehyde condensates, dialkylsulfosuccinates, dialkylphosphate salts, and sodium polyoxyethylene alkylphenyl ether sulfate; and fluorine-containing anionic surfactants such as perfluoroalkyl carboxylates, perfluoroalkyl sulfonates, and perfluoroalkyl phosphate esters.
[0067] Examples of the cationic surfactant include amine salts such as ethanolamines, laurylamine acetate, triethanolamine monoformate, and stearamidoethyl diethylamine acetate; and quaternary ammonium salts such as lauryl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, dilauryl dimethyl ammonium chloride, distearyl dimethyl ammonium chloride, lauryl dimethyl benzyl ammonium chloride, stearyl dimethyl benzyl ammonium chloride, tetrabutyl ammonium bromide, and lauryl trimethyl ammonium bromide.
[0068] Examples of the nonionic surfactants include polyoxyethylene higher alcohol ethers such as polyoxyethylene isodecyl ether, polyoxyethylene lauryl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkylaryl ethers such as polyoxyethylene octylphenol and polyoxyethylene nonylphenol; polyoxyethylene acyl esters such as polyoxyethylene monolaurate and polyoxyethylene monostearate; polyoxyethylene sorbitan fatty acid esters such as polypropylene glycol ethylene oxide adduct, polyoxyethylene sorbitan monolaurate, and polyoxyethylene sorbitan monostearate; phosphate esters such as alkyl phosphate ester and polyoxyethylene alkyl ether phosphate ester; sugar esters, and cellulose ethers.
[0069] Examples of the amphoteric surfactant include fatty acid type amphoteric surfactants such as dimethylalkyl lauryl betaine, dimethylalkyl stearyl betaine, lauryl dimethylaminoacetate betaine, and lauric acid amidopropyl dimethylaminoacetate betaine; sulfonic acid type amphoteric surfactants such as dimethylalkyl sulfobetaine; and alkyl glycines.
[0070] From the viewpoint of obtaining good anti-fogging performance with a relatively small amount, the surfactant (D) is preferably an anionic surfactant alone, a combination of an anionic surfactant and a cationic surfactant, or a combination of an anionic surfactant and an amphoteric surfactant. In particular, when the anionic surfactant is a fluorine-containing anionic surfactant, the surface tension of the anti-fogging film against water can be more effectively reduced, and therefore higher anti-fogging performance can be obtained.
[0071] The surfactant (D) is preferably 1 part by mass or more and 35 parts by mass or less relative to 100 parts by mass of the copolymer (A). From the viewpoint of improving the antifogging properties of the antifogging film, the surfactant (D) is more preferably 3 parts by mass or more and even more preferably 5 parts by mass or more relative to 100 parts by mass of the copolymer (A), and from the viewpoint of improving transparency, the surfactant (D) is more preferably 30 parts by mass or less and even more preferably 25 parts by mass or less.
[0072] <Water(E)> The water (E) of the present invention is a medium containing water, such as ion-exchanged water, distilled water, or industrial water, as a main component.
[0073] The water (E) is 650 parts by mass or more relative to 100 parts by mass of the copolymer (A). From the viewpoint of decreasing the viscosity of the antifogging agent composition and improving coating workability, the water (E) is preferably 1000 parts by mass or more relative to 100 parts by mass of the copolymer (A), and from the viewpoint of maintaining an appropriate viscosity of the antifogging agent composition and improving coating workability, the water (E) is preferably 4500 parts by mass or less, more preferably 3500 parts by mass or less.
[0074] The antifogging agent composition of the present invention may contain an organic solvent in order to improve coating workability or to use the composition as a polymerization reaction solvent in synthesizing the copolymer (A).
[0075] The organic solvent may be the same as the polymerization solvent described above, and among these, from the viewpoint of relatively low occurrence of solvent cracking, alcohol-based solvents and alcohol ether-based solvents are preferred, propanol, isopropanol, diacetone alcohol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, 3-methoxybutanol, and 3-methoxy-3-methylbutanol are more preferred, and propanol, isopropanol, diacetone alcohol, propylene glycol monomethyl ether, 3-methoxybutanol, and 3-methoxy-3-methylbutanol are even more preferred. The organic solvent may be used alone or in combination of two or more kinds.
[0076] When the antifogging agent composition of the present invention contains the organic solvent, the mass ratio of the organic solvent to the water (E) (organic solvent / water (E)) is preferably 0.3 or less, and more preferably 0.2 or less, from the viewpoint of suppressing the occurrence of solvent cracking.
[0077] When the antifogging agent composition of the present invention contains the organic solvent, the amount of the organic solvent (referred to as the VOC amount) is desirably 150 g / L or less from the viewpoint of environmental consideration. The VOC amount is calculated by multiplying the mass of the organic solvent contained in 1 kg of the antifogging agent composition by the specific gravity of the antifogging agent composition.
[0078] The antifogging agent composition of the present invention may contain a curing catalyst from the viewpoint of enabling heat curing at a low temperature in a short time.
[0079] Examples of the curing catalyst include fatty acid alkali metal salts such as sodium laurate, potassium laurate, calcium laurate, barium laurate, sodium oleate, potassium oleate, calcium oleate, barium oleate, sodium stearate, potassium stearate, calcium stearate, barium stearate, and fluoroalkyl fatty acid sodium salts; inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid; aromatic sulfonic acids such as p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and naphthalenesulfonic acid; and tertiary amines such as tetramethylbutanediamine, 1,4-diazabicyclo[2,2,2]octane, 1,8-diazabicyclo[5,4,0]-7-undecene, and 1,5-diazabicyclo[4,3,0]-5-nonene. Among these, from the viewpoint of improving low-temperature curing properties, fatty acid alkali metal salts are preferred, sodium laurate, potassium laurate, calcium laurate, barium laurate, sodium oleate, potassium oleate, calcium oleate, barium oleate, sodium stearate, potassium stearate, calcium stearate, and barium stearate are preferred, and sodium laurate, potassium laurate, sodium oleate, potassium oleate, sodium stearate, and potassium stearate are more preferred. The curing catalysts may be used alone or in combination of two or more.
[0080] When the curing catalyst is used, the amount of the curing catalyst is preferably 0.01 to 30 parts by mass, more preferably 0.05 to 15 parts by mass, and even more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the copolymer (A). When a fatty acid alkali metal salt is selected as the surfactant (D) and the curing catalyst, the amount of the fatty acid alkali metal salt used may be 20 parts by mass or less based on 100 parts by mass of the copolymer (A).
[0081] A leveling agent may be added to the antifogging agent composition of the present invention from the viewpoint of making the surface of the antifogging film smoother.
[0082] Examples of the leveling agent include polyether-modified polydimethylsiloxane, polyether-modified polydimethylpolysiloxane, polyether macromer-modified acrylate, acrylic polymer, and acrylic silicone polymer.
[0083] Examples of commercially available leveling agents include those under the trade names "BYK-300", "BYK-320", "BYK-306", "BYK-307", "BYK-310", "BYK-313", "BYK-315N", "BYK-320", "BYK-322", "BYK-323", "BYK-325", "BYK-330", "BYK-331", "BYK-333", "BYK-342", "BYK-345 / 346", "BYK-347", "BYK-348", "BYK-349", "BYK-370", "BYK-377", "BYK-378", "BYK-3455", and "BYK-3560" (all manufactured by BYK-Chemie Co., Ltd.). Product names include "KP-323", "KP-341", "KP-104", "KP-110", "KP-112", "KF-351A", "KF-352A", "KF-353", "KF-354L", "KF-355A", "KF-651A", "KF-945", "KF-640", and "KF-642" (all manufactured by Shin-Etsu Silicone Co., Ltd.), and product names include "Disparlon 1970", "Disparlon 230", "Disparlon 1711EF", "Disparlon 1761", "Disparlon LS-001", "Disparlon LS-050", "Disparlon LS-460", and "Disparlon LS-480" (all manufactured by Kusumoto Chemical Co., Ltd.). The leveling agents may be used alone or in combination of two or more kinds.
[0084] When the leveling agent is used, the amount of the leveling agent is preferably 0.05 to 25 parts by mass, more preferably 0.10 to 25 parts by mass, and still more preferably 0.5 to 20 parts by mass, relative to 100 parts by mass of the copolymer (A).
[0085] In addition to the above-mentioned components, the antifogging agent composition of the present invention may contain various conventional additives such as antioxidants, ultraviolet absorbers, light stabilizers, etc. The amount of the other components added may be the conventional amount for each additive, and is usually 10 parts by mass or less per 100 parts by mass of the copolymer (A).
[0086] <Anti-fog articles> The anti-fogging article of the present invention is one in which the anti-fogging agent composition is applied to a substrate (subject to be coated) by a coating method used for ordinary paints, and then heat-cured to form an anti-fogging film on the surface of the substrate (subject to be coated). Note that a drying step can be provided before the heat-curing step in order to volatilize and dry the solvent contained in the anti-fogging film immediately after coating.
[0087] The substrate (object to be coated) may be of any type and is not particularly limited, and examples thereof include resin substrates such as polymethyl methacrylate resin, polycarbonate resin, polystyrene resin, acrylonitrile-styrene copolymer resin, polyvinyl chloride resin, acetate resin, ABS resin, polyester resin, polyamide resin, etc.; inorganic substrates such as glass, etc. The shape of the substrate is not limited, and examples thereof include films, sheets, and three-dimensional molded products.
[0088] When coating the substrate (subject to be coated), it is preferable to remove any foreign matter adhering to the surface of the substrate (subject to be coated) before coating in order to increase the wettability of the antifogging agent composition to the substrate (subject to be coated) and prevent repellency. Examples of the method include dust removal using high-pressure air or ionized air, ultrasonic cleaning using a detergent aqueous solution or an alcohol solvent, wiping using an alcohol solvent, and cleaning using ultraviolet light and ozone. Examples of the coating method include immersion, flow coating, roll coating, bar coating, and spray coating.
[0089] The drying is usually carried out under conditions of a temperature of 20 to 50° C. for 0.5 to 10 minutes.
[0090] When the substrate is a resin member, the heating temperature is preferably set to a temperature equal to or lower than the thermal deformation temperature of the resin member. The heating time is affected by the heating temperature and should be set appropriately. For example, when the heating temperature is 80°C, the heating time is preferably 10 minutes or more, more preferably 15 minutes or more, and when the heating temperature is 130°C, the heating time is preferably 5 minutes or more, more preferably 10 minutes or more.
[0091] From the viewpoint of obtaining good anti-fogging properties and good coating appearance, the thickness of the anti-fogging film is preferably about 0.5 to 20 μm, and more preferably about 1 to 10 μm.
[0092] The antifogging article is more suitable for use in an environment where condensation is likely to occur, and is not limited in its use. Examples of the antifogging article include vehicle lighting (headlights, auxiliary headlights, width lights, license plate lights, tail lights, parking lights, back-up lights, turn signals, auxiliary turn signals, emergency flashers, etc.) for automobiles, glasses, windows, mirrors, etc. EXAMPLES
[0093] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.
[0094] <Synthesis example A-1> <Production of Copolymer (A-1)> A reaction vessel equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube was used, and 120 g of 3-methoxy-3-methylbutanol was charged as a polymerization solvent, stirring was started, and the mixture was heated to 70° C. while blowing in nitrogen gas. Next, the following monomer solution and polymerization initiator solution were added dropwise to the reaction vessel over a period of 2 hours. Monomer solution: A solution obtained by mixing 50 g of N,N-dimethylacrylamide as monomer (a-1), 25 g of hydroxyethyl methacrylate ε-caprolactone 2 mole adduct ("Placcel FM2D", Daicel Corporation, molecular weight 358) as monomer (a-2), 25 g of cyclohexyl methacrylate as monomer (a-3), and 20 g of 3-methoxy-3-methylbutanol as a polymerization solvent. Polymerization initiator solution: A solution obtained by mixing 0.71 g of t-hexyl peroxypivalate ("Perhexyl PV", NOF Corporation, active ingredient 70% by mass) as a polymerization initiator and 10 g of 3-methoxy-3-methylbutanol as a polymerization solvent. After the dropwise addition of the monomer solution and the polymerization initiator solution was completed, the solution in the reaction vessel was stirred for 3 hours to obtain a copolymer (A-1) having a concentration of 40 mass%. ) solution was prepared. The number average molecular weight of the copolymer (A-1) was measured by gel permeation chromatography under the above-mentioned measurement conditions, and was found to be 18,000. The amount of OHmol contained in 100 parts by mass (effective ingredient equivalent) of the copolymer (A-1) was calculated to be 25 / 358=0.070mol, since the amount of FM2D (monomer (a-2)) was 25 parts by mass and the molecular weight was 358g / mol.
[0095] <Synthesis example B-1> <Production of (meth)acrylate copolymer (B-1) having blocked isocyanate groups> A reaction vessel equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube was used, and 120 g of 3-methoxy-3-methylbutanol was charged as a polymerization solvent, stirring was started, and the mixture was heated to 70° C. while blowing in nitrogen gas. Next, the following monomer solution and polymerization initiator solution were added dropwise to the reaction vessel over a period of 2 hours. Monomer solution: A solution obtained by mixing 55 g of N,N-dimethylacrylamide as monomer (b-1), 15 g of diethyl malonate-blocked isocyanate group-containing acrylate ("Karenz MOI-DEM") as monomer (b-2), 30 g of butyl methacrylate as monomer (b-3), and 20 g of 3-methoxy-3-methylbutanol as a polymerization solvent. Polymerization initiator solution: A solution obtained by mixing 0.71 g of t-hexyl peroxypivalate ("Perhexyl PV", NOF Corporation, active ingredient 70% by mass) as a polymerization initiator and 10 g of 3-methoxy-3-methylbutanol as a polymerization solvent. After the dropping of the monomer solution and the polymerization initiator solution was completed, the solution in the reaction vessel was stirred for 3 hours to produce a copolymer (B-1) solution with a concentration of 40% by mass. The number average molecular weight of the copolymer (A) was measured by gel permeation chromatography under the above-mentioned measurement conditions, and was found to be 18,000. The amount of NCO mol contained in 100 parts by mass (effective ingredient equivalent) of the (meth)acrylate copolymer (B-1) having a blocked isocyanate group was calculated to be 15 / 315=0.048 mol, since the amount of MOI-DEM (monomer (b-2)) was 15 parts by mass and the molecular weight was 315 g / mol.
[0096] <Synthesis examples A-2 to A-17, comparative synthesis examples A-18 to A-21> In each synthesis example and comparative synthesis example, solutions of copolymer (A) of synthesis examples A-2 to A-17 and comparative synthesis examples A-18 to A-21 were produced in the same manner as synthesis example A-1, except that the monomer of synthesis example A-1 was changed to the monomer and its blending amount shown in Tables 1 to 3.
[0097] <Synthesis examples B-2~B-9> In each synthesis example, solutions of blocked polyisocyanate curing agent (B) of Synthesis Examples B-2 to B-9 were produced in the same manner as in Synthesis Example B-1, except that the monomer of Synthesis Example B-1 was changed to the monomer and its blending amount shown in Table 4.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Table 3]
[0101] [Table 4]
[0102] In Tables 1 to 4, monomers (a-1) to (a-5) and (b-1) to (b-3) are DMAA is N,N-dimethylacrylamide; DEAA, N,N-diethylacrylamide; FA1 is an adduct of hydroxyethyl acrylate with 1 mole of ε-caprolactone (product name: "Placcel FA1", manufactured by Daicel Corporation, molecular weight 230); FA2D is an adduct of hydroxyethyl acrylate with 2 moles of ε-caprolactone (product name: “Placcel FA2D”, manufactured by Daicel Corporation, molecular weight 344); FM2D: hydroxyethyl methacrylate ε-caprolactone 2 mole adduct (product name: "Placcel FM2D", manufactured by Daicel Corporation, molecular weight 358); FM3: hydroxyethyl methacrylate 3-mol adduct of ε-caprolactone (product name: “Placcel FM3”, manufactured by Daicel Corporation, molecular weight 473); FM5: hydroxyethyl methacrylate adduct with 5 moles of ε-caprolactone (product name: "Placcel FM5", manufactured by Daicel Corporation, molecular weight 701); FA10L is an adduct of hydroxyethyl acrylate with 10 moles of ε-caprolactone (product name: "Placcel FA10L", Daicel Corporation, active ingredient 70% by mass, molecular weight 1258); MMA, methyl methacrylate; EMA, ethyl methacrylate; BMA, n-butyl methacrylate; CHMA, cyclohexyl methacrylate; EHA is 2-ethylhexyl acrylate; LA, lauryl acrylate; SA is stearyl acrylate; HEA, hydroxyethyl acrylate; HEAA, hydroxyethylacrylamide; MOI-DEM is diethyl malonate-blocked 2-isocyanatoethyl methacrylate (product name: Karenz MOI-DEM, manufactured by Showa Denko K.K., molecular weight 315); AOI-BP: dimethylpyrazole-blocked 2-isocyanatoethyl acrylate (product name: Karenz AOI-BP, manufactured by Showa Denko K.K., molecular weight 237); MOI-BP: dimethylpyrazole-blocked 2-isocyanatoethyl methacrylate (product name: Karenz MOI-BP, manufactured by Showa Denko K.K., molecular weight 251); AOI-BM: methyl ethyl ketone oxime-blocked 2-isocyanatoethyl acrylate (product name: Karenz AOI-BM, manufactured by Showa Denko K.K., molecular weight 228); MOI-BM: methyl ethyl ketone oxime-blocked 2-isocyanatoethyl methacrylate (product name: Karenz MOI-BM, manufactured by Showa Denko K.K., molecular weight 242); Shows.
[0103] <Example 1> <Production of antifogging agent composition> To 250 g of the copolymer (A-1) solution obtained above, 275 g of (meth)acrylate copolymer (B-1) having a blocked isocyanate group was added as a blocked polyisocyanate curing agent (B), 500 g of water-dispersed silica sol ("Snotex O-40" manufactured by Nissan Chemical Industries, Ltd., active ingredient 40% by mass) as colloidal silica (C), 20 g of sodium di-2-ethylhexyl sulfosuccinate ("Rapizol A-80" manufactured by NOF Corp., active ingredient 80% by mass) as a surfactant (D), and 2945 g of ion-exchanged water as water (E) were added. Furthermore, 1 g of potassium oleate was added as a curing catalyst, and 1 g of polyether-modified polydimethylsiloxane ("KF-351A" manufactured by Shin-Etsu Silicone Co., Ltd.) as a leveling agent was added and mixed to produce an antifogging agent composition. The content of water (E) in Table 5 indicates the total of water derived from ion-exchanged water and water-dispersed silica sol, and the content of organic solvent indicates the total of organic solvent derived from components such as the copolymer (A-1) solution. The specific gravity of the obtained antifogging agent composition was measured using a hydrometer in accordance with JIS B 7523-3, and was 1.04. Since the amount of organic solvent contained in 1 kg of this antifogging agent composition was 78.8 g, the VOC amount was calculated to be 78.8 x 1.04 = 82 g / L. The NCO / OH ratio was calculated as follows. {NCO mol of (B-1) x mass part of (B-1) (effective ingredient equivalent)} / {OH mol of (A-1) x mass part of (A-1) (effective ingredient equivalent)} = {0.048 x 110} / {(0.070 x 100} = 0.75
[0104] The results obtained by using the antifogging agent composition obtained above and the following evaluation methods are shown in Table 5.
[0105] <Evaluation of Solvent Crack Resistance> In an environment set at 25°C, a 3 mm thick polycarbonate resin plate was bent by applying a stress of 120N to 150N using an autograph, and the antifogging agent composition obtained above was applied so that the wet film thickness was about 3 μm. After application, the plate was left in the same environment for 2 minutes. The test piece prepared by the above method was visually observed and evaluated according to the following four stages. Note that if the evaluation was B- or higher, there was no problem in practical use, if it was B+, it was preferable, and if it was A, it was more preferable. A: When a stress of 150N is applied, no cracks or breaks are observed in the base material. B+: No cracks or breaks are observed in the base material when a stress of 140N is applied. B-: No cracks or breaks are observed in the base material when a stress of 130N is applied. C: When a stress of 120N is applied, cracks, breaks, etc. are observed in the base material.
[0106] <Preparation of anti-fogging article> The anti-fog composition obtained above was spray-coated on a 3 mm-thick polycarbonate (PC) resin plate so that the anti-fog film after curing would have a thickness of about 5 μm, and the plate was heat-cured at 130° C. for 20 minutes to produce an anti-fog article (test piece) having an anti-fog film.
[0107] The test pieces obtained above were used in the evaluation methods described below, and the results are shown in Table 5.
[0108] <Transparency evaluation> In accordance with the test method for total light transmittance of plastic materials (JIS-K7361-1), a haze meter ("HAZE METER HDN5000", manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure the haze value of the test piece (light source: white LED, luminous flux: 14 mm, temperature: 25°C, humidity: 50%) and rated on the following four-point scale. Note that a rating of B- or higher means no problem for practical use, B+ is preferable, and A is more preferable. The haze value of a 3 mm thick PC resin plate was 0.30. A: 0.30 or more, less than 0.40 B+: 0.40 or more, less than 0.50 B-: 0.50 or more, less than 0.60 C:0.60 or more
[0109] <Evaluation of anti-fogging properties> <Steam test> The test piece was placed 5 cm above the water surface of a hot water bath kept at 80°C, with the anti-fogging film side facing down, and the anti-fogging film was continuously irradiated with steam from the hot water bath. The presence or absence of fogging 10 seconds after irradiation was visually evaluated on the following four-point scale. Note that if the evaluation was B- or higher, there would be no practical problem, if it was B+, it was preferable, and if it was A, it was more preferable. A: A water film is formed immediately after steam irradiation and the glass does not become cloudy. B+: A momentary cloudiness is observed immediately after steam irradiation, but a water film is quickly formed and the cloudiness disappears. B-: Clouding is observed immediately after steam irradiation, but a water film is eventually formed and the clouding disappears. C: Clouding was observed immediately after steam irradiation, and no water film was formed.
[0110] <Steam test after moisture resistance test> The test piece was left to stand for 240 hours under conditions of 50°C and 95% RH, and then left to stand for 1 hour at room temperature. After that, the test piece was placed 5 cm above the water surface of a hot water bath kept at 80°C, with the anti-fogging film side facing down, and the anti-fogging film was continuously irradiated with steam from the hot water bath. The presence or absence of fogging 10 seconds after irradiation was visually evaluated according to the following four stages. Note that if the evaluation is B- or higher, there is no problem in practical use, if it is B+, it is preferable, and if it is A, it is more preferable. A: A water film is formed immediately after steam irradiation and the glass does not become cloudy. B+: A momentary cloudiness is observed immediately after steam irradiation, but a water film is quickly formed and the cloudiness disappears. B-: Clouding is observed immediately after steam irradiation, but a water film is eventually formed and the clouding disappears. C: After steam irradiation, a clear water film is not formed, or no water film is formed and cloudiness is observed.
[0111] <Steam test after heat resistance test> The test piece was left to stand at 120°C for 240 hours, and then at room temperature for 1 hour. The test piece was then placed 5 cm above the water surface of a hot water bath kept at 80°C, with the anti-fogging film side facing down, and the anti-fogging film was continuously irradiated with steam from the hot water bath. The presence or absence of fogging 10 seconds after irradiation was visually evaluated according to the following four-point scale. Note that if the evaluation is B- or higher, there is no practical problem, if it is B+, it is preferable, and if it is A, it is more preferable. A: A water film is formed immediately after steam irradiation and the glass does not become cloudy. B+: A momentary cloudiness is observed immediately after steam irradiation, but a water film is quickly formed and the cloudiness disappears. B-: Clouding is observed immediately after steam irradiation, but a water film is eventually formed and the clouding disappears. C: After steam irradiation, a clear water film is not formed, or no water film is formed and cloudiness is observed.
[0112] <Evaluation of Adhesion> The anti-fog film of the test piece was cut into an area of 1 cm length and 1 cm width at 1 mm intervals in both directions using a cutter knife to create 100 grids. Cellophane tape was pressed onto the surface of the grid, and the appearance when it was quickly peeled off was visually observed and rated on the following three-level scale. A rating of B or higher was acceptable for practical use, and A was more preferable. A: No peeling was observed at all. B: Slight peeling is observed at the intersection of the cuts. C: Partially peeled off or completely peeled off.
[0113] <Water resistance evaluation> The test piece was left in 40°C hot water for 240 hours, and then left at room temperature for 1 hour, after which the anti-fogging film appearance was visually evaluated according to the following three stages: A score of B or higher is satisfactory for practical use, and A is more preferable. A: There is no change in appearance from before the test. B: The surface of the anti-fog film is slightly rough. C: The surface of the anti-fog film is rough or slightly whitened or stained.
[0114] <Examples 2 to 31 and Comparative Examples 1 to 9> <Production of antifogging agent composition and preparation of antifogging article> Antifogging compositions of Examples 2 to 31 and Comparative Examples 1 to 9 were produced in the same manner as in Example 1, except that the raw materials of Example 1 were changed to the raw materials and their blending amounts shown in Tables 5 to 8. Furthermore, antifogging articles (test pieces) having antifogging films of Examples 2 to 31 and Comparative Examples 1 to 9 were produced in the same manner as in Example 1. The content of water (E) in Tables 5 to 8 indicates the total of ion-exchanged water and water derived from water-dispersed silica sol. The results obtained by the above evaluation method using the obtained antifogging compositions and test pieces are shown in Tables 5 to 8.
[0115] [Table 5]
[0116] [Table 6]
[0117] [Table 7]
[0118] [Table 8]
[0119] In Tables 5 to 8, as the blocked polyisocyanate curing agent (B), "Aqua BI200" is an isocyanurate of hexamethylene diisocyanate blocked with anionic dimethylpyrazole (product name: "Aqua BI200" manufactured by BAXENDEN Co., Ltd., active ingredient 40% by mass, NCO amount 4.5% by mass, NCO mol per 100 g 0.13); "Aqua BI220" is an isocyanurate of hexamethylene diisocyanate blocked with nonionic dimethylpyrazole (product name: "Aqua BI200" manufactured by BAXENDEN Co., Ltd., active ingredient 40% by mass, NCO amount 4.2% by mass, NCO mol per 100 g 0.10); "WM44-L70G" refers to an isocyanurate of hexamethylene diisocyanate blocked with a malonic acid ester (product name: "Duranate WM44-L70G" manufactured by Asahi Kasei Corporation, active ingredient 70% by mass, NCO amount 5.3% by mass, NCO mol per 100 g 0.13);
[0120] In Tables 5 to 8, colloidal silica (C) is ST-OS is a water-dispersed silica sol with an average particle size of 8 to 10 nm (product name: "Snowtex OS", manufactured by Nissan Chemical Industries, Ltd., active ingredient 20% by mass); ST-O: water-dispersed silica sol with an average particle size of 10 to 15 nm (product name: "Snowtex O", manufactured by Nissan Chemical Industries, Ltd., active ingredient 20% by mass); ST-O-40 is a water-dispersed silica sol with an average particle size of 20 to 25 nm (product name: "Snowtex O-40", manufactured by Nissan Chemical Industries, Ltd., active ingredient 40% by mass); ST-OL: water-dispersed silica sol with an average particle size of 40 to 50 nm (product name: "Snowtex OL", manufactured by Nissan Chemical Industries, Ltd., active ingredient 20% by mass); ST-MP-1040: water-dispersed silica sol with an average particle size of 70 to 130 nm (product name: "Snowtex MP-1040", manufactured by Nissan Chemical Industries, Ltd., active ingredient: 40% by mass); ST-NS: water-dispersed silica sol with an average particle size of 8 to 10 nm (product name: "Snowtex NS", manufactured by Nissan Chemical Industries, Ltd., active ingredient 20% by mass); ST-N: water-dispersed silica sol with an average particle size of 10 to 15 nm (product name: "Snowtex N", manufactured by Nissan Chemical Industries, Ltd., active ingredient 20% by mass); ST-N-40 refers to a water-dispersed silica sol having an average particle size of 20 to 25 nm (product name: "Snowtex N-40", manufactured by Nissan Chemical Industries, Ltd., active ingredient 40% by mass);
[0121] In Tables 5 to 8, surfactant (D) is Rapisol A-80: sulfosuccinic acid diester salt (trade name: "Rapisol A-80", manufactured by NOF Corporation, active ingredient 80% by mass); FT-100 is a fluorine-containing anionic surfactant (sodium sulfonate) (product name: "Ftergent 100", manufactured by Neos Co., Ltd.); FT-150 is a fluorine-containing anionic surfactant (sodium sulfonate + sodium carboxylate) (product name: "Ftergent 150", manufactured by Neos Co., Ltd.); TBAB: tetra n-butylammonium bromide; 2-DB-500E: didecyldimethylammonium chloride (product name: "Nissan Cation 2-DB-500E", manufactured by NOF Corporation, active ingredient 50% by mass); ID-209: polyoxyethylene isodecyl ether (product name: "Nonion ID-209", manufactured by NOF Corporation); L-4 is polyoxyethylene monolaurate (trade name: "Nonion L-4", manufactured by NOF Corporation); BL-SF: lauryl dimethylaminoacetic acid betaine (product name: "Nissan Anon BL-SF", manufactured by NOF Corporation, active ingredient 36% by mass); BDL-SF: lauric acid amidopropyl dimethylaminoacetic acid betaine (product name: "Nissan Anon BDL-SF", manufactured by NOF Corporation, active ingredient 30% by mass);
[0122] In Tables 5 to 8, COASOL represents an organic solvent, which is a mixture of diisobutyl glutarate, diisobutyl succinate, and diisobutyl adipate (trade name: COASOL, manufactured by DAW CHEMICAL). As a leveling agent, KF351-A indicates polyether-modified polysiloxane (product name: KF351-A, manufactured by Shin-Etsu Silicones Co., Ltd.).
Claims
1. An antifogging agent composition comprising a copolymer (A), a blocked polyisocyanate curing agent (B), colloidal silica (C), a surfactant (D), water (E) and an organic solvent, The copolymer (A) is represented by the general formula (1): 【Chemistry 1】 (In general formula (1), R 1 is a hydrogen atom or a methyl group, R 2 and R 3 are independently a straight-chain or branched-chain alkyl group having 1 to 8 carbon atoms; and General formula (2): 【Chemistry 2】 (In general formula (2), R 4 is a hydrogen atom or a methyl group, and n is an integer of 1 to 10. General formula (3): 【Chemistry 3】 (In general formula (3), R 5 is a hydrogen atom or a methyl group, R 6 is a straight-chain, branched-chain, or cyclic hydrocarbon group having 1 to 22 carbon atoms; the blocked polyisocyanate curing agent (B) is 35 to 300 parts by mass, the colloidal silica (C) is 80 parts by mass or more and 600 parts by mass or less, and the water (E) is 650 parts by mass or more, relative to 100 parts by mass of the copolymer (A); An antifogging agent composition, characterized in that the mass ratio of the organic solvent to the water (E) (organic solvent / water) is 0.31 or less.
2. The antifogging agent composition according to claim 1, characterized in that, relative to a total of 100 parts by mass of the monomer (a-1), the monomer (a-2) and the monomer (a-3), the monomer (a-1) is 20 to 90 parts by mass, the monomer (a-2) is 5 to 50 parts by mass, and the monomer (a-3) is 1 to 40 parts by mass.
3. 3. The antifogging agent composition according to claim 1, wherein the amount of the surfactant (D) is 1 to 35 parts by mass based on 100 parts by mass of the copolymer (A).
4. The monomer mixture further comprises a monomer represented by general formula (4): 【Chemistry 4】 (In general formula (4), R 7 is a hydrogen atom or a methyl group, R 8 is a straight-chain or branched-chain alkylene group having 1 to 8 carbon atoms. 【Chemistry 5】 (In general formula (5), R 9 is a hydrogen atom or a methyl group, R 10 is a straight-chain or branched-chain alkylene group having 1 to 8 carbon atoms.
5. The antifogging agent composition according to claim 4, characterized in that the monomer (a-4) and / or the monomer (a-5) is 30 parts by mass or less per 100 parts by mass of the total of the monomer (a-1), the monomer (a-2), and the monomer (a-3).
6. The antifogging agent composition according to any one of claims 1 to 5, wherein the blocked polyisocyanate curing agent (B) is a (meth)acrylate polymer and / or copolymer having a blocked isocyanate group.
7. The blocked polyisocyanate curing agent (B) is represented by the general formula (6): 【Chemistry 6】 (In general formula (6), R 11 is a hydrogen atom or a methyl group, R 12 and R 13 are independently a straight-chain or branched-chain alkyl group having 1 to 8 carbon atoms; and General formula (7): 【Chemistry 7】 (In general formula (7), R 14 is a hydrogen atom or a methyl group, R 15 is a residue derived from a blocking agent; General formula (8): 【Chemistry 8】 (In general formula (8), R 16 is a hydrogen atom or a methyl group, R 17 is a straight-chain, branched-chain, or cyclic hydrocarbon group having 1 to 22 carbon atoms.
8. The antifogging agent composition according to claim 7, characterized in that, relative to a total of 100 parts by mass of the monomer (b-1), the monomer (b-2) and the monomer (b-3), the monomer (b-1) is present in an amount of 20 to 90 parts by mass, the monomer (b-2) is present in an amount of 5 to 50 parts by mass, and the monomer (b-3) is present in an amount of 1 to 40 parts by mass.
9. An anti-fogging article comprising an anti-fogging film formed from the anti-fogging agent composition according to any one of claims 1 to 8 on a substrate.
Citation Information
Patent Citations
Thermocouple thermometer
JP1988075531A
Anti-fogging coating, Anti-fogging molding, and production method of the Anti-fogging coating
JP2005036177A
Hydrophilic coating composition and hydrophilic member using it
JP2008308661A
Antifog coating composition
JP2011140589A
Antifogging agent composition
JP2016027134A